Matrix Stone Occupying an Entire Renal Collecting System: A Case Report and Video of Diagnostic Ureterorenoscopy. (23rd April 2018) - Cobley, Jonathan; Phan, Yih Chyn; Mahmalji, Wasim
Abstract : Renal matrix stones are a rare phenomenon and they present a diagnostic challenge due to their atypical radiological appearances in comparison to more commonly encountered renal tract calculi. We describe a case of known stone former presenting with loin pain and recurrent urinary tract infections who was diagnosed with a matrix stone. The video of the diagnostic flexiureterorenoscopy demonstrating the matrix stone occupying almost the entire right renal collecting system is also presented.